Remote Sensing from Space Supporting International Peace and Security - Jasani, Bhupendra; Pesaresi, Martino; Schneiderbauer, Stefan; Zeug, Gunter (Springer Netherlands : Imprint: Springer, 2009)
This volume provides the reader with an overview of the state-of-the-art Earth Observation (EO) related research that deals with national and international security. An interdisciplinary approach was adopted in this book in order to provide the reader with a broad understanding on the uses of remote sensing technologies. The book therefore comprises management aspects (issues and priorities of security research, crisis response), applied methodologies and process chains (treaty monitoring, estimation of population densities and characteristics, border permeability models, damage assessment) and the latest developments in generic tools (feature recognition, change detection and visualization). Moreover, issues of data sharing and standards, as well as new approaches to training security relevant techniques, are addressed. The contributing authors are leading researchers and experts from private companies, national research institutions and international organizations, all of whom were brought together under the aegis of the European research project GMOSS (Global Monitoring for Security and Stability). This book is tailored for the scientific community that deals with the application of EO data, as well as project managers and decision makers working in the field of security having an interest in technical solutions. The integrative use of many figures and sample images are ideal in enabling the non-technical reader to grasp quickly the modern technologies that are being researched in the area of civil security.